TOMATO RESEARCH ON THE EFFECTS OF DIFFERENT NUTRIENT MANAGEMENT AND MULCHING PRACTICES - Singh, Navdeep; Singh, Gurdeep (International Journal of Psychosocial Rehabilitation, 2021)
Recent years have seen a growth in the use of nutrient management and mulching techniques in tomato farming operations. Because of benefits such as a favourable soil temperature, reduced weed growth, moisture conservation, and greater crop output in India. Organic rice straw, soy bean straw mulch, and inorganic HDPE plastic are mainly included in the mulch options and management of fertilizer. Also, practices of nutrient management are basically used by farmers to effectively manage nutrient inputs. Fertilizer management and mulch options included black inorganic HDPE plastic, organic rice straw, and soybean straw mulch, as well as nutrient management practices used by farmers to manage nutrient inputs. Researchers found that plant height, number of flowers per cluster, and SPAD values, as well as fruit weight and yield, were at their greatest levels. Fertilizer management and mulch options included black inorganic HDPE plastic, organic rice straw, and soybean straw mulch, as well as nutrient management practices used by farmers to manage nutrient inputs.